Pengaruh Lama Perendaman (Soaking) Terhadap Karakteristik Fisik-Sensoris Udang Vannamei Beku Jenis Peeled and Deveined - Elisa, Siti Nur; Putri, Desiana Nuriza; Warkoyo,; Suhaimi, Yahya (JURNAL AGROINDUSTRI HALAL, 2022)
This research aims to determine the long effects of soaking on the physical-sensory characteristics of frozen vannamei shrimp types PD (Peeled and Deveined) produced. This research was conducted at PT Istana Cipta Sembada Banyuwangi, using a simple Randomized Block Design research design with four treatments and two groups based on different research times. Soaking shrimps use a solution formula that has been determined by the company, consisting of turbo solution (non-phosphate) and STPP (phosphate). Four treatments of immersion time included P1 (6 hours), P2 (12 hours), P3 (18 hours), and P4 (24 hours). The test parameters observed were net recovery value, step loss, drip loss, cooking loss, and organoleptic (appearance, smell, taste, texture). Data were analyzed using analysis of variance (ANOVA) for parametric variables, followed by a DMRT follow-up test at a 95% confidence level (α = 0.05). In addition, the organoleptic value was obtained from the average organoleptic score of 5 panelists (2 trained panelists and three untrained panelists). The results showed that the soaking time did not have a significant effect (p > 0.05) on the observed physical-sensory quality values.